2014
DOI: 10.1155/2014/164863
|View full text |Cite|
|
Sign up to set email alerts
|

Current State of Off-Site Manufacturing in Australian and Chinese Residential Construction

Abstract: Many techniques have been implemented to make construction industry more productive. The key focus is on reduction of total duration, reduction in construction cost, improvements in the quality, achieving more sustainable development, and safer construction sites. One of the techniques, which is emerging in the last two decades, is the use of off-site manufacturing (OSM) within the construction industry. Several research projects and industry initiatives have reported the benefits and challenges of implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 15 publications
(25 reference statements)
1
36
0
Order By: Relevance
“…As [25] An incentive from the government for programme was ranked as the third method to improve the implementation of construction robotics technologies.The government had introduced the Construction Industry Transformation Programme (CITP), 2016-2020, to propel the industry forward and meet the market demand [19]. This is followed by incentives for investment tax allowance can help to improve the implementation of construction robotics technologies where the allowance on qualifying plant and equipment acquired by the company during the ITA period can help to the company [26] The implementations of technologies were unattractive because it requires higher capital cost, and lack of support especially from clients towards the adoption of the technologies [27].…”
mentioning
confidence: 99%
“…As [25] An incentive from the government for programme was ranked as the third method to improve the implementation of construction robotics technologies.The government had introduced the Construction Industry Transformation Programme (CITP), 2016-2020, to propel the industry forward and meet the market demand [19]. This is followed by incentives for investment tax allowance can help to improve the implementation of construction robotics technologies where the allowance on qualifying plant and equipment acquired by the company during the ITA period can help to the company [26] The implementations of technologies were unattractive because it requires higher capital cost, and lack of support especially from clients towards the adoption of the technologies [27].…”
mentioning
confidence: 99%
“…The proportion of labor cost accounted for 9-32% of the PFC production cost in our study, though previous studies revealed that labor requirement be reduced compared with in traditional on-site construction [9,19]. The results were due to lack of technical personnel and lower productivity of continuous production in prefabrication, which brought with the high labor cost.…”
Section: Effect Of Productivity Index (Pi) On Capital Costmentioning
confidence: 64%
“…Similar terms of prefabrication can be found in research: such as industrialized building (Malaysia), prefabricated building, preassembly, modularization and off-site fabrication (USA), mass production, modern method of construction and off-site construction (UK, Japan and Singapore) [5,9,28,38]. Similar to traditional on-site construction, prefabrication can be used to form a variety of architectures and functions, including residential, commercial buildings and infrastructure [11].…”
Section: Methodsmentioning
confidence: 84%
“…Whilst critiques highlight recurrent challenges viz 'mirroring' fragmented practices (cf. coordination and process integration); proponents (on balance), proffer a myriad of solutions for mitigating these negative issues see - Arashpour et al (2018); Khalfan and Maqsood (2014); Pan and Goodier (2012); Pan et al 2007. The management of construction projects typically follows professional frameworks and industry best practices embodied in official guidelines such as the Project Management Body of Knowledge also known as PMBOK (PMI 2015) or the Projects in Controlled Environment also known as PRINCE2 (TSO 2009). As advocated by both frameworks, one of the most fundamental tools used in these frameworks and guidance is the work breakdown structure (WBS).…”
mentioning
confidence: 99%